2003
DOI: 10.1002/hep.1840380428
|View full text |Cite
|
Sign up to set email alerts
|

Myeloperoxidase–Positive Inflammatory Cells Participate in Bile Duct Damage in Primary Biliary Cirrhosis Through Nitric Oxide–Mediated Reactions

Abstract: Previous studies have suggested that increased nitric oxide (NO)-mediated products are found in the livers of subjects with primary biliary cirrhosis (PBC), but the mechanisms involved remain enigmatic. We took advantage of immunohistochemistry and several unique monoclonal antibodies to study inflammatory cells responsible for the generation of NO, the enzymes responsible for NO production, the expression of 3-nitrotyrosine, and the presence of CD68(+) and/or myeloperoxidase (MPO)(+) cells. We examined a tota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2006
2006
2010
2010

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(19 citation statements)
references
References 21 publications
0
19
0
Order By: Relevance
“…The expressions of p21 WAF1/Cip1 and 8-OHdG were evident in the nuclei of hepatocytes in NASH in this study, as previously reported [21], suggesting that oxidative stress is involved not only in hepatocellular damage in NASH but also in biliary epithelial damage of small bile ducts showing CNSDC of PBC. There are several other reports that oxidative stress may be related to the pathogenesis of biliary epithelial damage in CNSDC followed by biliary epithelial apoptosis [11,28,29]. It is difficult to state that the oxidative stress related to p21 WAF1/Cip1 and 8-OHdG expression is a primary pathologic phenomenon of the bile ducts in PBC or a secondary event to inflammatory cell infiltration of PBC livers.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…The expressions of p21 WAF1/Cip1 and 8-OHdG were evident in the nuclei of hepatocytes in NASH in this study, as previously reported [21], suggesting that oxidative stress is involved not only in hepatocellular damage in NASH but also in biliary epithelial damage of small bile ducts showing CNSDC of PBC. There are several other reports that oxidative stress may be related to the pathogenesis of biliary epithelial damage in CNSDC followed by biliary epithelial apoptosis [11,28,29]. It is difficult to state that the oxidative stress related to p21 WAF1/Cip1 and 8-OHdG expression is a primary pathologic phenomenon of the bile ducts in PBC or a secondary event to inflammatory cell infiltration of PBC livers.…”
Section: Discussionmentioning
confidence: 91%
“…For example, Tinmouth et al reported that the apoptosis of BECs in PBC is secondary to intense periductal inflammation [9]. In particular, the infiltration of MPO-expressing cells and eosinophils around the bile ducts is thought to be a candidate generator of oxidative stress in PBC [11,28,29]. At present, it seems at least partly possible that the intraepithelial infiltration of MPO-positive cells is rather characteristic of damaged bile ducts in PBC as well as chronic hepatic allograft rejection, and the oxidative stress donors are MPO-positive intraepithelial-infiltrating cells of damaged bile ducts [11,16].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In addition, the immunostaining score for gp210 antigens was positively correlated to the degree of portal inflammation, interface hepatitis and lobular inflammation. Therefore, we speculate that the increased immunoreactivity of gp210 antigen of BECs in PBC is possibly associated with various conditions including a putative attack by antigen-specific T cells [16e18], an effect of various proinflammatory cytokines [19], a state of increased apoptosis with glutathione depletion [20], increased nuclear DNA fragmentation and Bcl-2 expression [21,22], active lipid peroxidation [23], induction of inducible nitric oxide synthase (iNOS) and reactive oxygen species (ROS) [24,25], and increased expression of p53 and WAF1(p21 cip1/WAF1 ) [26].…”
Section: Discussionmentioning
confidence: 99%
“…In our previous study of 19 PSC patient liver biopsies, 84% of patients with PSC had inflammatory cells localized to the portal area, although only four (21%) were found to have inflammatory cells infiltrating the small bile ducts. When compared with normal subjects, PSC (P<0.0001) had a significantly higher number of tissue sections with CD68-and/or MPO-positive cells in the portal areas [59].…”
Section: Innate Immune Response In Pscmentioning
confidence: 99%